Focal hepatic glycogenosis - Bannasch, Peter; Jahn, Uli-Rüdiger; Hacker, Hans Jörg; Su, Qin; Hofmann, Walter J.; Pichlmayr, Rudolf; Otto, Gerd (International journal of oncology, 1997)
Foci of altered hepatocytes (FAH) including clear cell foci excessively storing glycogen (focal hepatic glycogenosis) are well known as preneoplastic lesions in animal models of hepatocarcinogenesis induced by chemical, physical or viral agents. The occurrence of similar lesions has been studied in a series of 67 explanted and 2 resected human livers using histological and histochemical approaches. A high incidence of FAH was found in the liver of patients suffering from hepatocellular carcinoma(HCC, 14/14) and liver cirrhosis (21/42). FAH were also detected in one patient each with inborn hepatic glycogenosis type 1a, and cholangiocellular carcinoma. Two patients with focal nodular hyperplasia had FAH-like enzymatic changes within these lesions. No FAH were found in 5 donor livers. FAH excessively storing glycogen including clear and mixed cell foci predominated in most cases with these lesions. The focal hepatic glycogenosis was associated with a significantly increased cell proliferation compared to the extrafocal parenchyma, and with alterations in the activity of various enzymes. In the 175 FAH studied by enzyme histochemistry, two enzymes involved in glycogen breakdown, namely glycogen phosphorylase and glucose-6-phosphatase, showed the most consistent changes, being reduced in 98% and 95%, respectively. In addition, the activities of adenosine triphosphatase and gamma-glutamyltransferase were reduced in 46% and 53% of FAH, respectively. Inconsistent changes were observed in FAH concerning a number of other enzymes. The 14 HCCs investigated histochemically often contained clear cell populations rich in glycogen in well differentiated portions, but were poor in glycogen in moderately and poorly differentiated tumors or tumor components. There were some similarities in the enzyme histochemical pattern of HCC and FAH but also important differences were evident. In contrast to FAH, all HCCs (except one carcinoma of the fibrolamellar type) showed an increase in the activity of the mitochondrial glycerol-3-phosphate dehydrogenase, and 50% of the cases had increased glucose-6-phosphate dehydrogenase activity. The activities of glucose-6-phosphatase and gamma-glutamyltransferase usually showed a reactivation, or even an increase compared to the extrafocal parenchyma, in moderately and poorly differentiated HCCs. Our results indicate that the focal hepatic glycogenosis is a putative preneoplastic lesion in human beings similar to laboratory animals. The focal hepatic glycogenosis appears to be a frequent initial step in neoplastic transformation of hepatocytes, a process associated with a fundamental shift in energy metabolism.